Theory and measurement of environmental unpredictability - Young, Ethan S.; Frankenhuis, Willem E.; Ellis, Bruce J. (Evolution and human behavior, 2020)
Over the past decade, there is increasing interest in the ways in which environmental unpredictability shapes human life history development. However, progress is hindered by two theoretical ambiguities. The first is that conceptual definitions of environmental unpredictability are not precise enough to be able to express them in statistical terms. The second is that there are different implicit hypotheses about the proximate mechanisms that detect unpredictability, which have not been explicitly described and compared. The first is the ancestral cue perspective, which proposes that humans evolved to detect cues (e.g., loss of a parent, residential changes) that indicated high environmental unpredictability across evolutionary history. The second is the statistical learning perspective, which proposes that organisms estimate the level of unpredictability from lived experiences across development (e.g., prediction errors encountered through time). In this paper, we address both sources of ambiguity. First, we describe the possible statistical properties of unpredictability. Second, we outline the ancestral cue and statistical learning perspectives and their implications for the measurement of environmental unpredictability. Our goal is to provide concrete steps toward better conceptualization and measurement of environmental unpredictability from both approaches. Doing so will refine our understanding of environmental unpredictability and its connection to life history development.